2011
DOI: 10.1172/jci42754
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Cxcr2 disrupts tumor-stromal interactions and improves survival in a mouse model of pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC), one of the most lethal neoplasms, is characterized by an expanded stroma with marked fibrosis (desmoplasia). We previously generated pancreas epithelium-specific TGF-β receptor type II (Tgfbr2) knockout mice in the context of Kras activation (mice referred to herein as Kras+Tgfbr2 KO mice) and found that they developed aggressive PDAC that recapitulated the histological manifestations of the human disease. The mouse PDAC tissue showed strong expression of connective tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
228
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 218 publications
(240 citation statements)
references
References 46 publications
(72 reference statements)
12
228
0
Order By: Relevance
“…Previous reports have also described CTGF as a critical mediator of vascular remodeling by regulating pericyte function and endothelial basement membrane formation during angiogenesis (43). In the tumor microenvironment, CTGF and the CXCR2 chemokine ligand axis have also been implicated as promoters of tumor angiogenesis in a variety of PDA models (42,44). In contrast to the prior finding that inhibition of CXCR2 resulted in reduced CTGF levels and regulated blood vessel density and tumor growth in the related Ptf1a cre/+ ;LSL-Kras G12D/+ ;Tgfbr2 flox/flox mouse model (44), FG-3019 had no effect on mean vessel density over the time course of treatment in KPC mice, and suggests that the relevant therapeutic targets here are neoplastic cell-intrinsic.…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports have also described CTGF as a critical mediator of vascular remodeling by regulating pericyte function and endothelial basement membrane formation during angiogenesis (43). In the tumor microenvironment, CTGF and the CXCR2 chemokine ligand axis have also been implicated as promoters of tumor angiogenesis in a variety of PDA models (42,44). In contrast to the prior finding that inhibition of CXCR2 resulted in reduced CTGF levels and regulated blood vessel density and tumor growth in the related Ptf1a cre/+ ;LSL-Kras G12D/+ ;Tgfbr2 flox/flox mouse model (44), FG-3019 had no effect on mean vessel density over the time course of treatment in KPC mice, and suggests that the relevant therapeutic targets here are neoplastic cell-intrinsic.…”
Section: Discussionmentioning
confidence: 98%
“…CXCR2 deficiency could inhibit inflammation-driven tumorigenesis in skin and intestine as well as spontaneous adenocarcinoma formation (36). CXCR2 has been proved to be a potent protumorigenic chemokine receptor that directs recruitment of tumor-promoting leukocytes into tissues in both tumor initiation stage and tumor promotion stage (37). Therefore, CXCR2 receptor antagonists are a potential pharmacologic approach in cancer and chronic inflammatory diseases (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…(19) Because the clinical and histopathological manifestations of Kras G12D +Tgfbr2 KO mice recapitulate human PDAC, these mice are considered a good model of human PDAC and are used for the evaluation of candidate treatment drugs for PDAC. (20) In the present study, we examined the role of JNK and the effect of JNK inhibition in pancreatic cancer using pancreatic cancer cell lines and Kras G12D +Tgfbr2 KO mice. We found that inhibition of JNK can be a potential therapy for pancreatic cancer.…”
mentioning
confidence: 99%